Antimicrobial efficacy of a hemilabile Pt(II)-NHC compound against drug-resistant S. aureus and Enterococcus - Kaur, Mandeep; Thakare, Ritesh; Bhattacherya, Arindom; Murugan, Prem Anand; Kaul, Grace; Shukla, Manjulika; Singh, Alok Kr; Matheshwaran, Saravanan; Chopra, Sidharth; Bera, Jitendra K (Dalton transactions : an international journal of inorganic chemistry, 2023)
Three platinum(II)-N-heterocyclic carbene (NHC) compounds [Pt(L )Cl](PF ) (1), [Pt(L )(COD)](PF ) (2) and [Pt(L )Cl ] (3) were synthesized bearing pyridyl-functionalized butenyl-tethered (L H) and -butyl tethered (L H) NHC ligands, and their antibacterial activity against clinically relevant human pathogens was evaluated. Complex 1 was designed to have one of its metal coordination sites masked with a hemilabile butenyl group. The antibacterial activity spectrum against the ESKAPE panel of pathogens shows superior activity of 1 compared to 2 and 3 against the Gram-positive pathogen. Complex 1 showed equipotent activity against clinical drug-resistant and isolates. Furthermore, 1 demonstrated concentration-dependent bactericidal activity with a long post-antibiotic effect, eradicated preformed biofilm and synergized with gentamicin and minocycline for combinatorial antimicrobial therapy. Under conditions, 1 displayed potent activity in reducing bacterial load in a murine thigh infection model, similar to vancomycin, albeit at 2.5× less dosage. An array of experiments reveals key characteristics for the hemilabile complex 1 as a potential anti-staphylococcal drug.